2019
DOI: 10.3389/fncel.2019.00368
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Altered BDNF/TrkB Signaling in Amyotrophic Lateral Sclerosis

Abstract: Brain derived neurotrophic factor (BDNF) is well recognized for its neuroprotective functions, via activation of its high affinity receptor, tropomysin related kinase B (TrkB). In addition, BDNF/TrkB neuroprotective functions can also be elicited indirectly via activation of adenosine 2A receptors (A 2a Rs), which in turn transactivates TrkB. Evidence suggests that alterations in BDNF/TrkB, including TrkB transactivation by A 2a Rs, can occur in several neurodegenerative diseases, including amyotrophic lateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
88
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(90 citation statements)
references
References 202 publications
(291 reference statements)
1
88
0
1
Order By: Relevance
“…The latter receptor is activated by adenosine that in turn transactivates TrkB and enhances the promotion of neuronal survival. 62 CD73 is a 5'-ectonucleotidase that specifically cleaves adenosine monophosphate to release adenosine. CD73 is highly abundant in the membrane of MSC-derived EVs and surface profiling has confirmed the presence of CD73 in the MSC-EV preparations.…”
Section: Discussionmentioning
confidence: 99%
“…The latter receptor is activated by adenosine that in turn transactivates TrkB and enhances the promotion of neuronal survival. 62 CD73 is a 5'-ectonucleotidase that specifically cleaves adenosine monophosphate to release adenosine. CD73 is highly abundant in the membrane of MSC-derived EVs and surface profiling has confirmed the presence of CD73 in the MSC-EV preparations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports suggested that PI3K/Akt and MEK/ERK1/2 signaling pathways regulate transcription activities including neurotrophic factors. The MEK/ERK1/2 pathway phosphorylates the transcription factor cAMP response element binding protein (CREB), which translocates into the nucleus and induces the transcription of BDNF and IGF-1 [ 55 , 56 , 57 , 58 ]. Recent studies have demonstrated that AKT and ERK1/2 also stimulate VEGF expression via HIF-1α activation [ 59 ] and that HGF production is upregulated by the RhoA-PI3K/Akt-MEK/ERK1/2 signaling axis [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the relevance of the BDNF/TrkB signaling pathway in synapses' regulation and maintenance, especially regarding the NMJ, it has been studied in pathologies where synaptic function is impaired. Specifically, the BDNF/TrkB signaling is strongly impaired in brains affected by ALS, and all the approaches used around it were summarized in a recent review [94]. The present review summarizes how the retrograde BDNF/TrkB signaling pathway and the downstream alteration of protein kinases C is disturbed from its physiological mechanism in ALS at the NMJ and how exercise and other therapies that modulate kinases are effective at delaying ALS's progression.…”
Section: Bdnf/trkb Signaling Is Impaired In Als Nmjmentioning
confidence: 99%
“…Thus, this adds new evidence of the relevance of BDNF being able to work, which spotlights the importance of the mechanism of activation of TrkB, which depends on the TrkB.FL/TrkB.T1 ratio. Indeed, in the absence of BDNF, TrkB can be transactivated through A2R [110] and mAChR [90] and has been proposed as a therapy for neurodegenerative diseases [94].…”
Section: Bdnf/trkb Signaling Is Impaired In Als Nmjmentioning
confidence: 99%